Experiences from assistive technology services and their delivery in Finland - Anne-Marie Tuikka; Neeraj Sachdeva (Switzerland, 2022)
The purpose of this article is to understand and document the level and quality of assistive technology (AT) driven rehabilitative support offered to people with impairments within Finland. Availability, accessibility and adoption of assistive technologies are of interest to this study. Currently public institutions, such as city hospitals and national social security institution, offer AT services generally on the basis of age, employment and individual needs. The main research question is, how people with impairments and their relatives perceive assistive technology delivery, use as well as continued adoption? Based on data, the different aspects of AT service delivery model and its relationship to rehabilitation process are described.
The empirical data is gathered through interviews and official documents including appropriate laws and guidelines published by public institutions. Analysis of the data highlights stages within the current system where negative experiences create distrust and dissatisfaction among AT adopters. These experiences are categorized to themes and stages which may be used for analyzing AT services and its relation to rehabilitation in future research. Further research would be needed to compare the applicability of the defined stages in analyzing delivering AT services in other countries – both similar and different to Finland.
Digital Nations – Smart Cities, Innovation, and Sustainability